Quantitative lexical comparison of novels of Indonesian writers before independence and the post-reformation period: study using a corpus linguistic approach - Vicno Triwira Dhika; Havid Ardi; Novia Juita; Norliza Jamaluddin (Cogent Arts & Humanities)
This research examines the lexical features of Indonesian literary works produced before independence and after the reform era. A quantitative comparison is conducted to analyze the variation in word usage between the pre-independence and post-reform periods of Indonesian literature. The corpus linguistic application used is the Korpus Nusantara (KORTARA) application. The research data consists of 5 corpuses of novels by Indonesian writers before independence and 5 corpuses of novels by Indonesian writers after reform. The results of this research reveal that in the novel corpus the average number of lexical types in the novel corpus of Indonesian writers from the pre-independence period is lower than in the novel corpus of Indonesian writers from the post-reformation period in Indonesia. This research also reveals a relationship between differences in lexical characteristics and the types of novel corpus in the two different periods. The differences in lexical characteristics between the novel corpus from the pre-independence period and the post-reform period are statistically significant at p < 0.05. The implication of this research is the realization of KORTARA with a corpus linguistic approach which can facilitate research for various corpora. This research also reveals that the application of a statistical approach provides maximum benefits in the analysis of linguistic phenomena.